Implementasi Kurikulum Merdeka pada Pembelajaran FIkih Kelas X di MAN 1 Jombang - Haj, Habil Syahril; Syari’ah, Atiris; Mulyono, Mulyono (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The purpose of this study is to examine how the Merdeka Curriculum is being implemented in fiqh learning at MAN 1 Jombang. The main focus of this research includes three aspects: the Merdeka Curriculum's implementation, including its design, execution, and assessment of learning, as well as the elements that facilitate and hinder it. A qualitative approach with a descriptive focus is the research methodology employed. Methods for gathering data include documentation, interviews, and observation. Data gathering, data presentation, and conclusion drawing are all part of data analysis. Data validity is ensured through source triangulation. The results of the study indicate that in the planning stage, teachers participated in socialization, training, and workshops, formed teaching teams, and prepared learning tools. The implementation of learning gives full freedom to teachers without intervention from the madrasah. Learning evaluation is based on learning outcome indicators focused on students, with initial assessments, formative assessments through discussions, presentations, and written reflections, and summative assessments that include written tests, observations, and performance sheets. Supporting factors include the availability of complete learning media, high enthusiasm and motivation from students, and adequate teacher competence. But there are a number of challenges, such time constraints and confusion among some teachers in implementing the new curriculum. The It is anticipated that the study's findings will enhance the caliber of fiqh instruction.